The Impact of Staff Engagement Towards the Institutional Quality Assurance Processes of Higher Education Institutions in the UAE - ASHOUR, RAZAN IZEDDIN (2025)
Quality assurance processes in higher education institutions remain extremely important to sustain academic standards at a high level and secure continuous improvement. However, there is limited understanding of how staff engagement affects these processes within the UAE's unique cultural and institutional context. This study, therefore, explores the role of staff engagement in enhancing the quality assurance processes of institutions in UAE higher education. It utilised a mixed-method approach of a quantitative survey and qualitative interviews with staff and managers from different higher education institutions. The quantitative results showed that awareness, support, and motivation are crucial drivers of staff engagement, although awareness was most strongly correlated with QA effectiveness. The qualitative results revealed inconsistent communication, variance of resources' allocation, high workloads, and other factors that may influence staff perceptions and engagement in QA. Additionally, the analysis revealed a significant gap between the institutional policies and staff engagement, underlining the need for specific approaches to address this issue. This study contributes to higher education policymakers, institutional leaders, and quality assurance professionals by providing evidence-based recommendations on the establishment of QA committees, the relevance of training, and recognition programmes as staff motivators. The findings emphasise that engagement, awareness, and support of staff are key to improving quality assurance processes and provide a foundation for future studies to explore strategies for adapting to the CAA transition to the Outcomes-Based Education Framework. The study provides a basis for future research and practical strategies for the improvement of educational quality and institutional performance in the UAE.